Cultivation of circulating tumor cells in esophageal cancer - Bobek, Vladimir; Matkowski, Rafal; Gürlich, Robert; Grabowski, Krysztof; Szelachowska, Jolanta; Lischke, Robert; Schützner, Jan; Harustiak, Tomas; Pazdro, Alexandr; Rzechonek, Adam; Kolostova, Katarina (Folia histochemica et cytobiologica, 2014)
The presence of circulating tumor cells (CTCs) in patients with metastatic carcinoma is generally associated with poor clinical outcome. There have been many investigations showing a possible use of CTCs as minimally invasive predictive and prognostic biomarker in cancer medicine. In this report a size-based method (MetaCell®) for quick and easy enrichment and cultivation of CTCs is presented to enable possible CTCs use in esophageal cancer (EC) management. In total, 43 patients with diagnosed EC, 20 with adenocarcinoma (AdenoCa) and 23 with squamous cell carcinoma (SCC), were enrolled into the adaptive prospective-like study .All the patients were candidates for surgery. The CTCs were detected in 27 patients (62.8%), with a higher rate in adenocarcinoma (75%) than SCC (52%). Finally, there were 26 patients with resectable tumors exhibiting CTCs-positivity in 69.2% and 17 patients with non-resectable tumors with 41.7% CTCs-positivity. Interestingly, in the patients undergoing neoadjuvant therapy, the CTCs were detected at time of surgery in 55.5% (10/18). The overall size-based filtration approach enabled to isolate viable CTCs and evaluate to their cytomorphological features by means of vital fluorescent staining. The CTCs were cultured in vitro for further downstream applications including immunohistochemical analysis. This is the first report of the successful culturing of esophageal cancer CTCs. The detection of CTCs presence could help in the future to guide timing of surgical treatment in EC patients.
Keywords: Esophageal Neoplasms; Adenocarcinoma; nádory jícnu; adenokarcinom; spinocelulární karcinom; Carcinoma, Squamous Cell; Filtration; počet buněk; Humans; Neoplastic Cells, Circulating; prospektivní studie; lidé; Prospective Studies; filtrace; barvení a značení; Cell Count; Staining and Labeling; nádorové cirkulující buňky